HUBUNGAN KELAS SOSIAL DALAM PEMBELIAN PAKAIAN SECOND HAND PADA MASYARAKAT KOTA TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Rahmanida Tiara; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research was conducted at Jongkok Market and Kayu Jati Market in Tembilahan, Indragiri Hilir Regency. The purpose of this study is to find out: 1) What is the social class of the people who buy Second hand in Tembilahan 2) Is there a relationship between social class and the purchase of second hand in the people of Tembilahan city. This research was a correlational quantitative research. The population of this research were people who bought used clothes at the Jongkok Market and Kayu Jati Market and the sample in this study were 100 respondents selected by using accidental sampling technique. Data instruments were Observations, Interviews and Questionnaires. Based on the results of the reserach it can be concluded that the social class of used clothing buyers based on indicator data on wealth, power, honor and knowledge was in the lower social class with a frequency of 58 respondents. The decision to bought used clothes was seen from the data on the stability indicator of buying after knowing the product information, deciding to bought because it was the most preferred brand, deciding to bought because it was in accordance with wants and needs, buying because it received recommendations from other people was at medium quality with a frequency of 67 respondents. Based on the calculation results of the correlation test, it was found that the Pearson product moment value was 0.599, the probability number was 0.00. The correlation coefficient value was 0.599 which lies in the range 0.4 – 0.59, it can be concluded the relationship between these variables was in the moderate category with a positive correlation, which means that the higher the social class of the buyer, the higher the quality of what their bought. Keywords: Social class, Buying Decision, Second Hand